A Systematic Review of Ceramic Nozzle Manufacturing: Methods, Strengths, Limitations, and Future Directions - Purnomo, Agung; Listyanda, R. Faiz; Ramadhan, Husnan Rizky; Putra, Juero Presinata (Program Studi Teknik Mesin Universitas Khairun, 2025)
Ceramic nozzles are used in a whole range of industrial applications, thanks to their excellent thermal, wear resistance, and durability in extreme environments. This study provides a Systematic Literature Review (SLR) leveraging PRISMA methodology evaluating methods, strengths, limitations, and future directions. This study groups together ceramic nozzle functions, production processes, strengths, and limitations to help determine the most productive fabrication approach. Findings reveal that conventional ceramic production methods allow for structural integrity, but modern additive manufacturing methods improve precision and scalability. Nevertheless, issues like brittleness and demanding manufacturing processes still pose major challenges. Emerging areas such as nano-ceramic composites, hybrid polymer, AI and machine learning-driven manufacturing, and sustainable sintering techniques can establish a new paradigm for performance and cost-effectiveness in future research. Moreover, pursuing biomedical and energy system applications would be another area of potential for ceramics material versatility and industrial relevance.